An innovative process for the treatment of high loaded surface waters for small communities. Issue 2 (1st March 2007) - Niquette, Patrick; Lahaye, Pierre; Lacasse, Maurice; Hausler, Robert
Abstract : Treatment trials have been realized with a new compact process in order to meet the drinking water regulation newly implemented in the province of Quebec. This process is especially designed for the supply of small communities. It combines complementary treatments operated by a centralized computer: ozonation, membrane filtration, and biological filtration, thus reducing operation to basic tasks. The process functioned very well for the period under review, in spite of extreme conditions met: cold water and constant fluctuation of the raw water quality. The process considerably lowers the contents of organic compounds (TOC, DOC, and color), the turbidity, the chlorine demand, and the concentrations of trihalomethane precursors present in the raw water. For this specific application, the backwash wastewaters may be mixed and discharged directly into a river nearby.